Analysis of Endoscopy Intervention in Postesophagectomy Anastomotic Leak: A Retrospective Study - Ma, Han; Wang, Jun; Xi, Qinhua; Shi, Dongtao; Zheng, Shiying; Ma, Haitao; Ge, Jinfeng (The Thoracic and Cardiovascular Surgeon, 2019)
Background Anastomotic leak after esophagectomy is one of the most challenging complications resulting in a high morbidity and mortality and prolonged hospitalization. The aim of this retrospective study was to access the impact of endoscopy intervention in anastomotic leak.Methods A retrospective review was conducted at our hospital from January 2008 to December 2016. In total, 263 patients who were diagnosed with an anastomotic leak after esophagectomy and underwent endoscopy examination were included in this study. First, all patients were divided into two groups based on a single criteria—whether they received endoscopy intervention or not—and comparisons were conducted between the two groups. Second, we categorized all patients into three groups based on the diameter of the anastomotic leak (group I: <5 mm; group II: 5–15 mm; group III: >15 mm). Detailed analyses were made for each group. Factors we considered included demographic factors, the length of postoperative hospital stay, the amount of medical expenditure, limited days of oral intake, and the incurrence of complications. Data relating to those factors were collected and then analyzed using standard statistic tools.Results In general, the difference between endoscopy intervention and conservative measure was significant. Moreover, the hospital stay (p < 0.001; p = 0.018), medical expenditure (p < 0.001; p = 0.003), limited days of oral intake (p < 0.001; p = 0.019), and postoperative complications such as hemorrhage (p < 0.001; p = 0.036), tracheoesophageal fistula (p = 0.002; p = 0.017), and anastomosis stricture (p = 0.03; p = 0.026) were significantly lower among patients who received endoscopy intervention in groups II and III. However, no significant difference was identified between endoscopy intervention and conservative measure in group I.Conclusions Endoscopy intervention is safe and effective in the diagnosis and treatment of postesophagectomy anastomotic leak. Especially for patients with a diameter of anastomotic leaks greater than 5 mm, the advantages of endoscopy intervention should not be neglected.
Keywords: esophageal surgery; quality of life; surgery; complications